Medical immigration: the elephant in the room. Issue 7620 (20th September 2007) - Winyard, Graham
Abstract : The threat of unemployment among UK graduates this year is being blamed on the new computerised recruitment system. But, argues Graham Winyard, the real problem is government policy on medical immigration